AB0924 Echocardiography Findings in Asymptomatic Hyperuricemic Patients with Silent Deposit of MSU Crystals. (9th June 2015) - Andrés, M.; Quintanilla, M.A.; Sivera, F.; Vela, P.; Ruiz-Nodar, J.M.
Abstract : Background: Both asymptomatic hyperuricemia (AH) and gout have been reported to associate with abnormal echocardiography findings, such as left ventricle hypertrophy (LVH) [1] or dyastolic dysfunction (DD) [2]. However, to date no study has focused on the echocardiography findings in AH patients with silent monosodium urate (MSU) crystal deposits. Objectives: To describe the echocardiography findings of a subgroup of AH patients with demonstrated MSU crystals deposit, and to compare with subgroups with normouricemia (NU) and AH without crystals. Methods: Cross-sectional study. Consecutive patients admitted due to an acute coronary event were screened for enrolment. Patients were classified according to the serum uric acid (SUA) level at admission as: AH (SUA>7.0 mg/dL and no history suggestive of gout) or NU (sustained SUA<7.0mg/dL on lab records). Those with current urate-lowering treatment were excluded. AH patients underwent US of both knees and 1st MTP joints in order to detect signs of crystal deposition; when present, arthrocentesis was performed to confirm MSU crystals by polarised light microscopy. These findings were confirmed by a blinded rheumatologist. All patients underwent transthoracic echocardiography during the admission, by an independent observer. The presence of the following echocardiography variables was assessed: a) moderate-severe LVH; b) moderate-severely decreased left ventricle ejection fraction (LVEF); c) grade II DD; d) moderate-severe aortic stenosis (AS); and e) moderate-severe mitral regurgitation (MR). Comparison between subgroups was performed. Regression was used to analyze the association between echocardiography variables and crystal deposits, adjusting for potential confounders. Results: 140 patients were enrolled, median (p25-75) age 71.5 years (61.0-79.8), 76.4% males. Sixty-six were NU and 74 AH; 13 (17.5%) of these were later classified as AH with crystals after US and arthrocentesis. Traditional CV risk factors distributed similarly between groups, except for hypertension and BMI, increased in both AH subgroups (but not differing between them). The Table shows the echocardiographic findings. Both AH subgroups showed higher prevalence of LVH and AS, but no significant differences were noted regarding the crystal status. No differences in the other echocardiography variables were found. In the regression analysis, the presence of MSU crystals did not associate with any of the echocardiographic variables evaluated. Conclusions: This is the first study assessing the echocardiographic findings of AH patients with demonstrated MSU crystals. The results suggest no apparent impact of these crystals on this outcome. References: Eur J Clin Invest. 44:972. PLoS One. 9:e108357. Disclosure of Interest: None declared